2017
DOI: 10.1021/acs.est.7b01472
|View full text |Cite
|
Sign up to set email alerts
|

Bifenthrin Causes Toxicity in Urban Stormwater Wetlands: Field and Laboratory Assessment Using Austrochiltonia (Amphipoda)

Abstract: Stormwater wetlands are engineered to accumulate sediment and pollutants from stormwater and provide environmental value to urban environments. Therefore, contaminated sediment risks causing toxicity to aquatic fauna. This research identifies contaminants of concern in urban wetland sediments by assessing sediment toxicity using the amphipod Austrochiltonia subtenuis. Sediments from 98 wetlands were analyzed for contaminants, and laboratory bioassays were performed with A. subtenuis. Wild Austrochiltonia spp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Aside from the general metal and hydrocarbon contamination, the widespread occurrence and elevated concentration of bifenthrin and triclosan are emerging concerns. Studies in Australia and elsewhere have reported environmental impacts of bifenthrin and other synthetic pyrethroids at similar concentrations to those observed here [ 36 , 37 , 38 , 39 , 40 ]. Triclosan, an antimicrobial used in many household products, has also recently been highlighted as a risk to environmental and human health [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Aside from the general metal and hydrocarbon contamination, the widespread occurrence and elevated concentration of bifenthrin and triclosan are emerging concerns. Studies in Australia and elsewhere have reported environmental impacts of bifenthrin and other synthetic pyrethroids at similar concentrations to those observed here [ 36 , 37 , 38 , 39 , 40 ]. Triclosan, an antimicrobial used in many household products, has also recently been highlighted as a risk to environmental and human health [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 84%
“…Sediments were analyzed for metals, pesticides, total organic carbon, petroleum hydrocarbons, polycyclic aromatic hydrocarbons (PAHs). Experimental details for sediment analysis have been published previously [ 34 , 35 , 36 ]. Briefly, University of Melbourne Chemistry Department analyzed the sediments for organic contaminants by GC-MS, including personal care products and selected pesticides.…”
Section: Methodsmentioning
confidence: 99%
“…Pyrethroids in surface waters and associated toxicity have been reported in many regions of the United States (Hintzen, Lydy, & Belden, ; Kuivila et al., ; Rogers et al., ). Internationally, they have been found in water bodies at concentrations of ecotoxicological concern in several South American countries (Hunt et al., ), England (Long, House, Parker, & Rae, ), Spain (Feo, Ginebreda, Eljarrat, & Barceló, ), China (Mehler, Li, Lydy, & You, ), and Australia (Jeppe et al., ). Additionally, while most studies documenting aquatic risk of pyrethroids in the United States have generally relied upon H. azteca , work elsewhere has reported toxicity to Chironomus dilutus (Mehler et al., ) and the amphipod, Austrochiltonia subtenuis (Jeppe et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, they have been found in water bodies at concentrations of ecotoxicological concern in several South American countries (Hunt et al., ), England (Long, House, Parker, & Rae, ), Spain (Feo, Ginebreda, Eljarrat, & Barceló, ), China (Mehler, Li, Lydy, & You, ), and Australia (Jeppe et al., ). Additionally, while most studies documenting aquatic risk of pyrethroids in the United States have generally relied upon H. azteca , work elsewhere has reported toxicity to Chironomus dilutus (Mehler et al., ) and the amphipod, Austrochiltonia subtenuis (Jeppe et al., ). Thus, it is possible, and even likely, that other species are exposed to the same pyrethroid‐related selective pressures we documented in H. azteca .…”
Section: Discussionmentioning
confidence: 99%
“…Levels of at least some organic pollutants likely differ between reference and stormwater sites, as the former receive water from direct rainfall and local runoff from adjacent paddocks, whereas runoff into the latter is predominantly from high-density residential and industrial areas. As an example, nearby sites in the upstream catchment have sediment concentrations of the insecticide bifenthrin above those that cause toxicity to crustacea (amphipods; Jeppe et al 2017). This could reduce zooplankton densities (predominantly crustacea) within contaminated sites, with flow-on effects to fish growth, reproduction, and survival.…”
Section: Aim 2: Can Fish Differentiate Between Stormwater and Referenmentioning
confidence: 99%